The new way of clean clothing - Vieira, Alexandre Silva Ministro (2022)
The purpose of this study is to determine a relation between supply chain concepts, as well as omnichannel retailing, and the laundry market. The aim is to relate the retail market with the laundry market, takings as basis e-commerce, with the expectation that a potential customer has the same behaviours when buying, within an e-commerce platform, in the retail market and in the laundry market. This is supported by a literature review in the fields of omnichannel, lastmile delivery, competitive advantage creation and customer behaviour, where the ongoing trends of e-commerce were identified. It was possible to identify that customers prefer digital solutions and online shopping, thus having a platform that merges the use of a mobile app with the physical service provided by the laundry companies will be a differentiating factor in the laundry market. Quantitative research conducted in the form of an online survey showed that the enquired population has interest in the value propositions presented to them, as most of the people that currently do their laundry at home were likely to recommend the idea to a friend or family member. The business plan elaborated to make the implementation of the idea possible identifies the key strategic, marketing, technological, organizational, and financial aspects, which allow for its evaluation, hypothetical funding, and implementation. The financial plan developed to analyse the viability of the project obtained encouraging results, as, considering demand predictions made, it would start generating profits from operations in less than 3 years.